PEMANFAATAN ARTIFICIAL INTELLIGENCE SEBAGAI ALAT BANTU PENGUJIAN APLIKASI VISUAL NOVEL MYSTIC PAGES MENGGUNAKAN METODE BLACK-BOX - Engka, Elisya Belia Maria; Fajar, Mohammad; Zaman, Baizul (KHARISMA Tech, 2026)
Application or software testing is one of the important stages in application development, as it ensures that the application meets the defined specifications or user requirements. This also applies to visual novel applications, which face challenges in the testing process, such as ensuring that the narrative runs smoothly and logically, and that the features work without any obstacles. This study aims to utilize Artificial Intelligence (AI) as a testing tool for the visual novel application Mystic Pages. The AI application Gemini is used to assist in the automatic generation of testing scenarios using equivalence partitioning and boundary value analysis techniques. Data collection was conducted through literature review, AI prompt testing, and the designed application. Evaluation showed that the Gemini AI used could generate structured, systematic, and easy-to-use test scenario outputs for equivalence partitioning and boundary value analysis techniques. If done manually without using Gemini AI, scenario descriptions took approximately 1 hour and 20 minutes to generate. Meanwhile, using Gemini AI only takes approximately 10 minutes. The Gemini AI prompt entered must include the Mystic Page application specification table and a request for scenario creation based on the desired technique. Additionally, the test scenarios generated by Gemini AI can be used to test the Mystic Page application.